The Re-use of the Classics as Intangible Cultural Heritage: : The “Dead Centre” Case - Malosio, Andrea (Mimesis Journal, 2024)
The theatre company Dead Centre was founded in Dublin in 2012 by Bush Moukarzel and Ben Kidd. The group has based its plays on the re-working of great Classics of literature, theatre and philosophy, combining the thinking and the biographies of authors from the past with the most modern languages and technological tools. The significative point in company’s work is the use of different languages: the intersection between actorly performativity, objects and machines; the use of headphone audio and the resulting immersion for actors and spectators; the role of the constant presence of videos on stage; the investigation about bodies.